Quasi $z^°$-submodules of reduced multiplication modules - Faranak Farshadifar (Journal of Mahani Mathematical Research)
‎The purpose of this paper is to define and investigate the notion of quasi $z^°$-submodules of modules over a commutative ring as an extension of $z^°$-ideals of commutative rings. Also, we obtain some related results when $M$ is a reduced multiplication $R$-module.